"Development and validation of a prediction model for bothersome stress urinary incontinence after prolapse surgery" by Oh et al. (5th January 2022) - van der Ploeg, J. Marinus; Steyerberg, Ewout W.
Abstract : Linked article: This is a mini commentary on S Oh et al., pp. 1158–1164 in this issue. To view this article visit https://doi.org/10.1111/1471-0528.17036